Deskripsi Kemampuan Membaca Siswa Melalui Pembelajaran Teaching at the Right Level (TaRL) di Sekolah Dasar - Mariamah, Mariamah; Nur, Fahyuni; Salmah, Siti; Jauhari, Jauhari (Bima Journal of Elementary Education, 2024)
The reading ability of elementary school students is an important aspect that needs to be improved so that students can understand other subjects well. However, the reality is that many students still face difficulties in reading, which impacts their ability to learn other subjects. This study aims to describe the reading ability of students through the implementation of the Teaching at the Right Level (TaRL) approach in elementary schools. This research employs a descriptive method with a sample of 25 students. The research instruments include tests and documentation, while data analysis is conducted using percentage formulas. The results indicate a significant improvement in students' reading levels: the beginner level decreased from 1% to 0%, indicating that students progressed to the letter level; the letter level decreased from 8% to 0%, indicating an increase in students moving to the word level; the word level decreased from 29% to 8%, showing that many students advanced to the paragraph level; and the story level increased from 33% to 62%. These results demonstrate that the Teaching at the Right Level (TaRL) approach is effective in improving the reading abilities of students who initially had low skills.